Investigating the Benefits and Challenges of Workplace Volunteering Experiences for International Students’ Employability Literacies - Barton, Georgina; Hartwig, Kay; Hu, Yijun; Kavanagh, Marie; Watson, Marthy (Journal of International Students, 2021)
For many international students the prospect of employment in overseas locations post-study is a strong desire. The concept of employability has infiltrated the literature but little is known about how volunteering experiences might impact international students’ preparedness for work placement during their programs of study. Using theoretical framing related to types of employability literacies, this paper shares data from interviews with international students who volunteered. Findings revealed several themes aligning with linguistic proficiency, cultural awareness, attitudes and mindset, and vocational literacies. Additional themes such as hospitable relationships and building trust were also revealed which could relate to sustainable citizenship. Many benefits result from volunteering experiences for both international students and their hosts, but more work is needed to support hosts through cultural awareness programs and international students due to their study commitments and limited time.